Target cum flexibility: simple access to benzofuran conjugated sugar and nucleoside derivatives - Kommagalla, Yadagiri; Srinivas, Kolluru; Ramana, C. V. (Tetrahedron Letters, 2013)
The [Pd]-catalyzed domino process comprising of the coupling of alkynes and o-iodophenol and the subsequent cyclization leading to benzofurans has been successfully applied on the sugar and nucleoside derived alkynes. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Benzofuran; carbohydrates; cyclization; Nucleoside; Palladium

Ru-catalyzed branched versus linear selective C3-alkylation of 2-aroylbenzofurans with acrylates via C-H activation - Kommagalla, Yadagiri; Srinivas, Kolluru; Ramana, Chepuri V. (Chemistry-A European Journal, 2014)
The carbonyl-directed C3-H activation and alkylation of 2-aroylbenzo[b]furans with acrylates occurs selectively either in a linear or branched fashion, depending on the catalyst employed; [Ru(p-cymene)Cl-2](2) or Ru(PPh3)(3)Cl-2, respectively. Two alternate pathways-funded upon the differences in steric and electronic preferences of these two complexes-is proposed for the selectivity of linear versus branched products.
Keywords: acrylate; benzo[b]furan; branched-selective alkylation; C-H activation; ruthenium

Cu-catalyzed sequential C-N bond formations: expeditious synthesis of tetracyclic indoloindol-3-ones - Kulkarni, Anand M.; Srinivas, Kolluru; Deshpande, Mukund V.; Ramana, Chepuri V. (Organic Chemistry Frontiers, 2016)
The tetracyclic indoloindol-3-one core has been forged from easily accessible 2,2'-bis-bromochalcones employing a reaction cascade comprising Cu-catalyzed SNAr with azide; nitrene C-H insertion and intramolecular Ullmann reaction with all three C-N bond formations in one-go.

Electronic control on linear versus branched alkylation of 2-/3-aroylbenzofurans with acrylates: combined DFT and synthetic studies - Srinivas, Kolluru; Dangat, Yuvraj; Kommagalla, Yadagiri; Vanka, Kumar; Ramana, Chepuri V. (Chemistry-A European Journal, 2017)
Investigations on the factors that govern unusual branched alkylation of 2-aroylbenzofurans with acrylates by Ru-catalyzed carbonyl-directed C-H activation has been carried out by calculating the kinetics associated with the two key steps-the coordination of the acrylate with the intermediate ruthenacycle and the subsequent migratory insertion reaction-studied with the help of DFT calculations. Eight possible orientations for each mode of alkylation have been considered for the calculations. From these calculations, it has been understood that there is a synergistic operation of the steric and electronic effects favoring the branched alkylation. Further DFT investigations on the alkylation of the isomeric 3-aroylbenzofurans indicated a preference for the linear alkylation and this has been verified experimentally. Overall, the observed/calculated complementary selectivity in the alkylation of 2-/3-aroylbenzofurans with acrylates reveals that the substrate-dependent charge distribution of the Ru-C bond in the intermediate ruthenacycle is an important determining factor and thus the current work opens up a new domain of substrate design for controlling regioselectivity.
Keywords: acrylates; Alkylation; aroylbenzofuran; C-H activation; Density functional calculations

Interrupting base-mediated benzofuran ring transformation with michael acceptors - Srinivas, Kolluru; Sharma, Rashmi; Ramana, Chepuri V. (Journal of Organic Chemistry, 2017)
A simple two-stage approach for the synthesis of 3-(2-arylbenzofuran-3-yl)propanoates and propanamides has been developed employing simple acrylates and acrylamides and readily available 3-aroylbenzofurans. The key step of this process involves a base-mediated ring opening of the 3-aroylbenzofurans and subsequent Michael addition of the resulting 1,3-dicarbonyl intermediate with acrylate/acrylamide, followed by the deformylation in one-pot. The resulting products undergo an acid-mediated dehydrative cyclization to arrive at these targets.
Keywords: Acyl Benzylic Bromides; Beta-Ketoaldehydes; Efficient Synthesis; Ortho-Hydroxybenzyl Ketones; Phenols; Position; Precursors; Sur Le Benzofuranne; Transposition

Total synthesis of propolisbenzofuran B - Srinivas, Kolluru; Ramana, Chepuri V. (Organic Letters, 2017)
An efficient synthesis of propolisbenzofuran B, which possesses promising anticancer activity, is reported. The key cyclohexanone framework of this tricyclic natural product has been constructed employing a Rh-catalyzed intramolecular olefin hydroacylation. The requisite key olefin intermediate was synthesized by using gold-catalyzed allenyl ether [1,3] O -> C rearrangement.

Ru(II)-catalyzed C-H activation/alkylation of 3-formylbenzofurans with conjugated olefins: product divergence - Srinivas, Kolluru; Siddiqui, Shaziyaparveen K.; Mudaliar, Jyothi K.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2019)
Ru-catalyzed alkylation of 3-formylbenzofuran with acrylates and acrylamides has been described. Branched selectivity with unsubstituted or beta-substituted acrylates/ acrylamides and linear selectivity with alpha-substituted acrylates have been observed. However, in all of the cases, the intermediate alkylation products seem to undergo further reactions, either cycloannulation or deformylation, depending on the substrate employed. For example, with methyl acrylate, the intermediate branched alkylation product underwent cycloannulation with another molecule of methyl acrylate, resulting in a densely functionalized cyclohexene ring formation. On the other hand, in the case of N-monosubstituted acrylamides, the branched alkylation proceeded with intramolecular aldehyde-amide condensation, leading to pyridin-2-one ring annulation. However, with both methacrylate and crotonate, deformylation of the initially formed alkylation products was observed.